ANALISIS TRANSPARANSI DAN PENGELOLAAN DANA ZAKAT PADA BAZNAS KABUPATEN MANDAILING NATAL - alfian, ian ian (WELFARE: Journal of Islamic Economics and Finance, 2024)
This research aims to find out how transparent and managed zakat funds are in BAZNAS, Mandailing Natal Regency. The method used is a qualitative approach. The results of the research are in accordance with article 71 paragraph (2), namely that the zakat funds collected are distributed to each BAZNAS program in Mandailing Natal Regency, namely through Madina Makmur, Madina Sehat, Madina Smart, Madina Peduli, Madina Taqwa. Meanwhile, for transparency, in accordance with Law Number 23 of 2011 concerning Management of Zakat Funds, each Regency/City is required to submit reports on the implementation of zakat management every 6 months and at the end of the year to the Provincial BAZNAS and Regent/Mayor.